Inviting eating disorder patients to discuss the academic literature: a model program for psychoeducation - Lauren Belak; Tara Deliberto; Matthew Shear; Sean Kerrigan; Evelyn Attia (Journal of Eating Disorders, 2017)
Abstract Background Psychoeducation initiatives in which patients read primary scientific literature have not yet been studied as a treatment intervention for eating disorders. In this paper, we discuss and evaluate the acceptability of a novel psychoeducational journal club for individuals with anorexia and bulimia nervosa in inpatient and partial hospitalization program settings. Primary literature about eating disorders is presented and discussed with patients. By presenting scientifically-supported information, our “Psychoeducational Research Group” is designed to help patients restructure disordered thoughts and encourage adherence to evidence-based treatment. Methods Using a Likert scale questionnaire (0 = not at all; 5 = very much), participants provided ratings for how much they liked the group and felt that it helped them across several domains. Results Average scores from 33 participants (26 inpatient, 7 partial hospital patients) indicated they would recommend this group to others receiving eating disorder treatment (4.8 ± 0.6). Scores also suggested patients’ likeability (4.6 ± 0.8), benefit regarding challenging eating disorder thoughts (4.1 ± 1.1), improved motivation for eating behavior change (4.0 ± 1.0) and completion of prescribed nutritional plan (3.6 ± 1.0), and usefulness in working towards treatment goals (4.2 ± 0.9) associated with group participation. Conclusions Preliminary findings support the acceptability of this psychoeducational group and that it may serve as a useful adjunct to larger evidence-based programming across eating disorder treatment settings.